Efficiency of Educational Production: An Analysis of New York School Districts - Ruggiero, John (The Review of Economics and Statistics, 1996)
Theoretical consideration of technical efficiency has existed since Tjalling C. Koopmans (1951), which defined technical efficiency for production possibilities for which it is impossible to increase any output without simultaneously increasing any input. The nonparametric approach to efficiency estimation is based not on this definition but rather on Michael J. Farrell's (1957) index. Even after Farrell efficiency is achieved, there may exist additional slack in individual inputs, implying that Farrell efficiency doesn't measure inefficiency. To solve this problem, this paper suggests incorporating programming results into a second-stage multivariate regression analysis. For illustrative purposes, this technique is applied to analyze New York State school districts. Copyright 1996 by MIT Press.